Why insight in psychotherapy does not always lead to behaviour change? - Kuncewicz, Dariusz; Lachowicz-Tabaczek, Kinga; Załuski, Jacek (Department of Psychology, University of Wrocław, 2014)
The purpose of this review was to come closer to answering the question why insight gained in psychotherapy does not necessarily lead to a change in patient’s behaviour. The review of literature on the subject of insight allowed us to distinguish two types of insight: “more intellectual than emotional” (I-e) and “more emotional than intellectual” (E-i). In addition, we differentiated E-i insight with a component of negative emotions (aversive) and with a component of positive emotions (corrective). We assumed that each type of insight would motivate the patient to change their behaviour in a different way. The I-e insight makes it easier for the patient to achieve concrete adaptive goals, the E-i aversive insight discourages them from attaining maladaptive goals, while the E-i corrective insight encourages them to form and follow adaptive goals. We also analysed the influence on behaviour change of some other factors, co-occurring with insight: the therapeutic relationship, the actions of the patient and his narrative motivation. Insight does not always lead to a change in behaviour because: 1) the type of the insight does not match the type of patient’s motivation; 2) insight occurs in the context of a weak therapeutic relationship or is not reinforced by the patient’s actions; 3) insight is not a key factor of change, but rather its effect or indicator.
Keywords: behaviour change; impulsive motivation; insight; narrative motivation; goal-oriented motivation